A New Interpretation for the Anomalous Channel-Length Dependence of Low-Frequency Noise in Quasi-Ballistic Transistors - Ajaykumar, Arjun (2018)
The operating regime of MOS transistors shifts from collision-dominated drift-diffusion (DD) to less-collision quasi-ballistic(QB) regime. The impact of transport mechanism on the low-frequency noise (LFN) is not well studied for QB devices. Most of the studies rely on the existing theories that were developed for DD-based devices to study LFN even in nanoscale regime. Validity of these models is questionable. In this letter, we extend the conventional carrier-number and correlated-mobility fluctuation model to the QB regime. The model is in accordance with the “apparent mean free path” (λapp) model, which predicts scattering limited noise mechanism in the QB regime. The model is validated with LFN measurement data for III-V QB devices, and shows good agreement with the expected behavior.